A Renewable Platform for High-Performance Glucose Sensor Based on Co(OH)2 Nanoparticles/Three-Dimensional Graphene Frameworks. Issue 2 (12th January 2019) - Du, Yongling; He, Yifeng; Zheng, Zhixiang; Shen, Xuan; Zhou, Yaxin; Wang, Tingxia; Zhu, Zhengping; Wang, Chunming
Abstract : Co(OH)2 nano particles (NPs)/three-dimensional graphene frameworks (3DGFs) nano-materials was fabricated via electrochemical methods. The Co(OH)2 NPs/3DGFs hybrid retain the 3DGFs's structure and have superior catalytic activity for glucose oxidation. The electrochemical sensors based on Co(OH)2 NPs/3DGFs exhibited high sensitivity of 2410 μA cm −2 mM −1, wide linear range of 2 μM to 1.4 mM, low detection limits of 0.67 μM and a quick response (less than 3s) to glucose. The Co(OH)2 NPs/3DGFs were used as a high performance platform to detect glucose in human serum, fetal bovine serum, and human urine. The excellent catalytic activity of Co(OH)2 NPs/3DGFs is attributed to the high surface area of 3DGFs and the highly catalytic activity of Co(OH)2 NPs as well as the synergistic effects between Co(OH)2 NPs and 3DGFs. Importantly, the electrochemical glucose sensor could be renewable only being refreshed in 0.1 M NaOH for ten minutes.